Safety of chia seeds (Salvia hispanica L.) subject to thermal processing in relation to the formation of process contaminants as a novel food for extended uses - Turck, Dominique; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; Siani, Alfonso; et al. (EFSA journal, 2020)
Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of chia seeds in foods subject to thermal processing which may result in the formation of process contaminants. The safety assessment of this novel food (NF) is based on previous assessments of chia seeds by the EFSA NDA Panel, information received from a public call for data by EFSA and information retrieved from an extensive literature search performed by EFSA. In 2019, during the overall safety assessment of chia seeds, the NDA panel retrieved one reference which, among others, investigated the formation of process contaminants, i.e. acrylamide, hydroxymethylfurfural and furfural, in wheat flour‐based biscuits with added chia seeds flour. Based on this study, the Panel considers that there is a potential for substantial acrylamide formation in biscuits with 10–20% added chia seeds flour with low residual moisture contents (≤ 2%). The Panel is not aware of further scientific evidence corroborating these findings. The extensive new literature searches performed by EFSA did not show any relevant articles regarding either asparagine content or formation of process contaminants in chia seeds and products thereof. Information received from the call for data were either limited or inconclusive. The available evidence does not provide a basis to conclude whether or not the addition of chia seeds to foods undergoing heat treatment (at temperatures above 120°C) results in increased formation of acrylamide as compared to these foods without chia seeds. Reported concentrations of hydroxymethylfurfural and furfural in heat‐treated chia seeds do not pose a safety concern. No information on other process contaminants in chia seeds was found. This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2020.EN-1925/full